PROBLEMATIKA AKSIOLOGIS PENDIDIKAN ISLAM Antara Moralitas vs Realita - Su'eb (LPPM STIT Miftahul Ulum Bangkalan, 2022)
This article tries to examine the problems that are being faced in Islamic education from an axiological review which is important to do. The method used by researchers is library research, which compares the concepts contained in the literature with research. As for the results, the axiological philosophy of Islamic education in Indonesia still has a fundamental weakness in presenting the formulation of objectives as part of the theory of knowledge. In addition, there are still many educational goals that are difficult to achieve or not yet applicable. So it can be concluded that the authors of the philosophy of Islamic education have had an academic awareness that the theory of objectives should have been formulated first before formulating the objectives of Islamic education from the perspective of philosophical studies. Unfortunately, this awareness was not realized by them and was not used as a guide to formulate the objectives of Islamic education in a systematic and comprehensive manner.